Higher extracellular water-to-total body water ratio more strongly reflects the locomotive syndrome risk and frailty than sarcopenia. (May 2020) - Tanaka, Satoshi; Ando, Kei; Kobayashi, Kazuyoshi; Nakashima, Hiroaki; Seki, Taisuke; Ishizuka, Shinya; Machino, Masaaki; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Kanemura, Tokumi; et al.
Highlights: The ECW/TBW ratio was higher in participants with LS risk, frailty, and sarcopenia. High ECW/TBW ratio strongly reflected late frailty stage and early LS risk stage. The ECW/TBW ratio is an important indicator in bioelectric impedance analysis. An increase in the ECW/TBW ratio may reflect locomotive syndrome risk and frailty. Abstract: Objective: Among body composition parameters measured by bioelectrical impedance analysis, the extracellular water-to-total body water (ECW/TBW) ratio is a known prognostic or related factor for various diseases. While concepts such as locomotive syndrome risk, frailty, and sarcopenia are gaining popularity in Japan, their relationship with the ECW/TBW ratio has not been examined in detail. This study aimed to investigate the relationships between them. Methods: Of 1081 individuals who underwent health checkups, 550 were included in this study. The evaluations included a two-step test, stand-up test, and a 25-question geriatric locomotive function scale questionnaire. Frailty was diagnosed based on the Japanese version of the Cardiovascular Health Study criteria. Sarcopenia was evaluated according to the Asian Working Group for Sarcopenia criteria. The aforementioned ratio was measured using bioelectrical impedance analysis. Results: The ECW/TBW ratio significantly increased with locomotive syndrome risk, frailty, and sarcopenia (p < 0.001 each). Nevertheless, no significant difference was found between robust and pre-frailty groups (p = 0.71) and normal and pre-sarcopenia groups (p = 0.93). Furthermore, after correcting for age, sex, and body mass index, multiple regression analysis revealed that locomotive syndrome risk (p < 0.001) and frailty (p = 0.001) were significantly associated with an increase in the ECW/TBW ratio, whereas sarcopenia was not (p = 0.97). Conclusions: An increase in the ECW/TBW ratio may reflect locomotive syndrome risk and frailty, but not sarcopenia. In bioelectric impedance analysis, this ratio is an important indicator; if it is high, it is necessary to consider locomotive syndrome risk and frailty.